2018
DOI: 10.1016/j.phytochem.2018.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic and other withanolides from aeroponically grown Physalis philadelphica

Abstract: Eleven withanolides including six previously undescribed compounds, 16β-hydroxyixocarpanolide, 24,25-dihydroexodeconolide C, 16,17-dehydro-24-epi-dioscorolide A, 17-epi-philadelphicalactone A, 16-deoxyphiladelphicalactone C, and 4-deoxyixocarpalactone A were isolated from aeroponically grown Physalis philadelphica. Structures of these withanolides were elucidated by the analysis of their spectroscopic (HRMS, 1D and 2D NMR, ECD) data and comparison with published data for related withanolides. Cytotoxic activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 23 publications
2
25
0
Order By: Relevance
“…The translinkage for the A/B ring was further verified by the negative Cotton effect around 340 nm in the ECD measurement of 1 [25], and the configurations at C-5, C-6, and C-7 were assigned accordingly, as depicted in Figure 1. The stereochemistry of H-22 (J = 13.5 and 3.5 Hz) was determined to be α-form on the basis of the typical coupling constants of H-22 reported in a previous study, where the 1 H NMR data of H-22α demonstrated a doublet of doublets with two different coupling constants (J = 9.0-13.8 and 0.5-4.0 Hz) [25,27], while the 1 H NMR data of H-22β showed two similar coupling constants (J = 2.5-7.0, 2.0-5.0 Hz) [28]. The α-orientation of H-22 was also verified by the ROESY correlations of H-16α/H-22 and H-17/H-22 (Figure 3).…”
Section: Structural Elucidation Of Compoundsupporting
confidence: 52%
See 1 more Smart Citation
“…The translinkage for the A/B ring was further verified by the negative Cotton effect around 340 nm in the ECD measurement of 1 [25], and the configurations at C-5, C-6, and C-7 were assigned accordingly, as depicted in Figure 1. The stereochemistry of H-22 (J = 13.5 and 3.5 Hz) was determined to be α-form on the basis of the typical coupling constants of H-22 reported in a previous study, where the 1 H NMR data of H-22α demonstrated a doublet of doublets with two different coupling constants (J = 9.0-13.8 and 0.5-4.0 Hz) [25,27], while the 1 H NMR data of H-22β showed two similar coupling constants (J = 2.5-7.0, 2.0-5.0 Hz) [28]. The α-orientation of H-22 was also verified by the ROESY correlations of H-16α/H-22 and H-17/H-22 (Figure 3).…”
Section: Structural Elucidation Of Compoundsupporting
confidence: 52%
“…The absolute configuration of 1 was determined by examining the correlations obtained from the ROESY experiment, vicinal proton coupling constants in the 1 H NMR data, and ECD data. The α-position of the epoxy group between C-6 and C-7 was confirmed by the ROESY correlations of H-7/H-8, H-6/H-7, H-6/ H3-19, and H3-19/H-8 and the characteristic coupling constant of 4.0 Hz between H-6 and H-7 (Figure 3), which also suggested a trans-linkage in the conformation of the A/B ring in 1, based on the smaller coupling constant of 0-2 Hz for H-6, which is typical in cis-linkages [25,27,28]. The translinkage for the A/B ring was further verified by the negative Cotton effect around 340 nm in the ECD measurement of 1 [25], and the configurations at C-5, C-6, and C-7 were assigned accordingly, as depicted in Figure 1.…”
Section: Structural Elucidation Of Compoundmentioning
confidence: 90%
“…Recently, husk tomato has been enjoying increasing attention in many countries, including Russia, due to new information on its chemical composition [4][5][6], health benefits, etc. [7][8][9][10][11]. Over the last few decades in Russia, the crop has been grown only by small farmers and individual gardeners; however, the last century saw quite a lot of attention paid to husk tomato.…”
Section: Introductionmentioning
confidence: 99%
“…Crushed leaves are applied over snakebites (Khan et al 2016). The medicinal benefits of P. philadelphica and P. ixocarpa are related to the presence of various bioactive phytochemicals, such as sucrose esters (Choi et al 2006;Xu et al 2018), and antiinflammatory .…”
Section: Chemical Composition Biological Activities and Use Of Physamentioning
confidence: 99%